The DYNAMICS AND SCIENTIFIC VISUALIZATION IN GENDER EQUALITY RESEARCH BASED ON ISLAMIC LAW: A BIBLIOMETRIC STUDY - Muchammad Rosyiid; Lismawati Lismawati (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the dynamics and scientific visualization of gender equality research based on Islamic law using bibliometric methods. Drawing on data from Scopus comprising 144 documents, the research employs a quantitative approach to identify publication trends, author collaboration patterns, geographic distribution, institutional affiliations, and the main emerging themes in the literature. The analytical methods include co-authorship, co-occurrence, and bibliometric coupling, visualized using VOSviewer and Microsoft Excel. The findings reveal a significant increase in publication volume beginning in 2018, peaking in 2024. Indonesia emerges as the leading contributor to this field, followed by the United Kingdom, Malaysia, and the United States. The research focuses on themes such as gender equality, Islamic law, and family law, with strong connections to human rights issues and legal reform. Thematic mapping indicates that normative issues and women's rights are dominant topics, while areas such as Islamic inheritance and gender mainstreaming are positioned as either emerging or declining. This study contributes to the mapping of scientific publications and offers strategic recommendations to strengthen interdisciplinary collaboration, expand data coverage, and promote Islamic legal reforms that are more responsive to gender equality.